Scanning Patterns of Faces do not Explain Impaired Emotion Recognition in Huntington Disease: Evidence for a High Level Mechanism - van Asselen, Marieke; Júlio, Filipa; Januário, Cristina; Bobrowicz Campos, Elzbieta; Almeida, Inês; Cavaco, Sara; Castelo-Branco, Miguel (Frontiers in Psychology, 2012)
In the current study, we aimed to investigate the emotion recognition impairment in Huntington’s disease (HD) patients and define whether this deficit is caused by impaired scanning patterns of the face. To achieve this goal, we recorded eye movements during a two-alternative forced-choice emotion recognition task. HD patients in pre-symptomatic (n = 16) and symptomatic (n = 9) disease stages were tested and their performance was compared to a control group (n = 22). In our emotion recognition task, participants had to indicate whether a face reflected one of six basic emotions. In addition, and in order to define whether emotion recognition was altered when the participants were forced to look at a specific component of the face, we used a second task where only limited facial information was provided (eyes/mouth in partially masked faces). Behavioral results showed no differences in the ability to recognize emotions between pre-symptomatic gene carriers and controls. However, an emotion recognition deficit was found for all six basic emotion categories in early stage HD. Analysis of eye movement patterns showed that patient and controls used similar scanning strategies. Patterns of deficits were similar regardless of whether parts of the faces were masked or not, thereby confirming that selective attention to particular face parts is not underlying the deficits. These results suggest that the emotion recognition deficits in symptomatic HD patients cannot be explained by impaired scanning patterns of faces. Furthermore, no selective deficit for recognition of disgust was found in pre-symptomatic HD patients.